تقييـم الكفـاءة التشغيليـة لقطـاع الرعايـة الصحيـة الوطنيـة دراســة تطبيقيــة - الياس, بومعراف (Recherches économiques et managériales; Vol. 15 (2014): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES(JUIN), 2014)
يواجه قطاع الرعاية الصحية الوطنية في الوقت الحالي تحديات هائلة متعلقة أساسا بقدرته على الاستجابة لحاجيات المجتمع الصحية. فالنمو السريع في استخدام الموارد المحدودة وتصاعد النفقات الصحية الوطنية بسبب نمو عدد السكان والزيادة في استخدام الرعاية الصحية الفردية، إضافة إلى التطورات الطبية التي فتحت الطريق لتوفير خيارات أكثر للعلاج والتشخيص دفعت بالطلب على الرعاية الصحية للارتفاع. وبالتالي تعد مسألة تحقيق نتائج صحية أكثر بأقل الموارد أهم تحدي تواجهه السلطات العمومية في الجزائر.    تحاول هذه الورقة تقييم كفاءة قطاع الرعاية الصحية الوطنية باستخدام دالة الإنتاج (Cobb-Douglas). الكلمات الدالة : الكفاءة التشغيلية، قطاع الرعاية الصحية، النفقات الصحية الوطنية، دالة الإنتاج (Cobb-Douglas).         Abstract     The national healthcare system is facing at present enormous challenges related mainly to its capacity to respond to the needs of the health community. The rapid growth in the use of limited resources and the escalating of the national health expenditure due to the population growth, the increase in the use of individual healthcare and medical advances that have opened the way to provide more options for treatment and diagnostics prompted the demand for health care to rise. Therefore, the mater of achieving best health outcomes with fewer resources is the most important challenge faced by the public authorities in Algeria.     This paper attempts to assess the efficiency of the national health care system using Cobb-Douglas Production function. Key words: Operational efficiency, health care, National Health expenditures , Cobb-Douglas Function.